Influence of feeding period on consumption and weight gain of pirarucu - Crescêncio, Roger; Ituassú, Daniel Rabello; Roubach, Rodrigo; Filho, Manoel Pereira; Cavero, Bruno Adan Sagratzki; Gandra, André Lima (Pesquisa Agropecuaria Brasileira, 2005)
The objective of this study was to verify pirarucu Arapaima gigas preferential time of feeding, and the influence of different feeding periods on consumption and weight gain of this species. Three treatments were tested: diurnal feeding (fish fed at 9h and 15h), nocturnal feeding (fish fed at 21h and 3h), and continuous feeding (fish fed at 9h, 15h, 21h and 3h). Each treatment was evaluated in triplicate, and each trial unit had eight fishes with 313 g average weight, stoked into a 1 m3 (1x1x1 m) net cage. The nine net cages were located on a 120 m2 earth pond. The trial lasted for 60 days. Continuous feeding promoted the highest weight and biomass gain, specific growth rate and feed consumption. Nocturnal and diurnal feeding treatments showed similar weight gain; however, diurnal feeding had the best feed conversion ratio. The preferred feeding time for pirarucu was the nocturnal period, mainly at the beginning of night. Data from this study indicated that the preferred feeding time is not the best one for feeding pirarucu on a commercial husbandry. The most indicated feeding period for this species, based on its feed conversion capacity, is diurnal period.